Tissue-based multigene expression tests for pretreatment prostate cancer risk assessment: current status and future perspectives. (15th August 2018) - Hiser, Wesley M; Sangiorgio, Valentina; Bollito, Enrico; Esnakula, Ashwini; Feely, Michael; Falzarano, Sara M
Prostate cancer is a highly prevalent disease with ample spectrum of aggressiveness and treatment options. Low-risk disease can be safely managed by nonintervention strategies, such as active surveillance; however, accurate risk assessment is warranted. Molecular tests have been developed and validated to complement standard clinicopathological parameters and help to improve risk stratification in prostate cancer. Herein, we review selected tissue-based assays, including genomic prostate score, cell cycle progression score and genomic classifier, with particular emphasis on their role in patient risk assessment in a pretreatment setting, in view of their current or potential utilization in active surveillance.